233k views
5 votes
Help me please
I don't know how to do this ​

Help me please I don't know how to do this ​-example-1
User Omortis
by
5.8k points

2 Answers

3 votes
I don’t either
Can someone please teach me
User Notdrone
by
5.7k points
6 votes
X = 1, Y = -1


You could do substitution :
x - y = 2
x = 2 + y
———————-
5(2 + y) + y = 4
10 + 5y + y = 4
10 + 6y = 4
6y = -6
y = -1
———————-
x - (-1) = 2
x + 1 = 2
x = 1
——————————
CHECK ANSWER :
5(1) + (-1) = 4
1 - (-1) = 2
User Carlos Alberto
by
6.4k points